Environmental Biotechnology - Hernández- Macedo, Maria Lucila (2020)
The various industrial sectors, as well as livestock and agricultural activities, are increasing the production of inputs to meet the demand of the worldwide demographic explosion, making a challenge the clean maintenance of water, soil, and air. Therefore, the search for solutions for a pollutant-free environment without compromising economic development has become extremely important. Thereby, biotechnological studies in order to solve environmental issues have been gaining extensive attention through the coupling of technology procedures to biological systems as sustainable solutions to remediate contaminated areas. In this sense, this review covers topics such as the role of Omics era in microbial environmental biotechnology for pollution control as well as the microbial fuel cell use in energy production. Moreover, phytoremediation and the perspective of applying chemical methods are approached as environmentally friendly tools for the pollutant control to improve remediation processes.